tingkat kesejahteraan pengrajin anyaman mensiang di jorong taratak nagari kubang kecamatan guguak kabupaten 50 kota - Elin Setia Gusni; afdhal afdhal (JURNAL BUANA, 2019)
Abstract This study aims to determine the level of well-being of woven craftsmen in Jorong Taratak Nagari Guguak Kabupaten 50 Kota. This type of research uses the descripyive method of the quantitative approach. The sampling technique uses total sampling whit a sample of 61 people. Data collection tools are questionnaires and data is processed using a percentage formula and uses a likert scale measuring instrument (Sugiyono 2003:86). Research result 1) the level of the woven craftsmen is in Jorong Taratak Nagari Guguak Kabupaten 50 Kota is classified as not prosperous, 39 (63,93%) respondents included in low welfare, 20 (32,79%) respondents included in moderate welfare, and 2 (3,28%) respondents who included high welfare. 2) the determinants of the level of welfare of the aging woven craftsmen are (a) population (b) health and nutrition (c) education (d) employment (e)level and pattern of consumption (f) housing and environment (g) proverti (h) other social indicators. In the determinants of welfare levels of several of the determinants above using the likert scale, none of which belong to the high welfare category.